Improved Predictive Power Control Algorithms to Increase CDMA System Capacity - Kurniawan, A.; Iskandar, Iskandar; Machdar, Sayid (Journal of Engineering and Technological Sciences, 2009)
In  this  paper  capacity  of  CDMA  system  is  evaluated  using  an improved  algorithm  of  channel  prediction-based  power  control  in  Rayleigh fading  channel environments. One  of the most serious problems which degrades the performance of power control algorithm is the effect of feedback delay. To overcome the effect of feedback delay, power control algorithm relies on channel prediction techniques, which utilize the correlation property of the past  channel measurements.  In  CDMA  power  control,  however,  the  correlation  property  of channel  measurements  is destroyed  because the  transmit power  is continuously updated  for  each  power  control  interval.  In  order  to  restore  the  correlation property of the channel,  the past  channel measurements  are compensated  for by the  same  factors  that  were  given  by  power  updating  for   each  power  control interval. The prediction algorithm in this paper is proposed using the least mean square  (LMS) technique. The result shows that the capacity of CDMA systems increase  significantly  when  the  improved  predictive  algorithm  is  used. Numerical evaluation shows that CDMA capacity increases by more than 40 % for fixed step algorithm and more than 50 % for variable step algorithm when the proposed algorithm is employed.